METODE PELAKSANAAN PONDASI BORE PILE PADA PEKERJAAN PENANGANAN LONGSORAN PROYEK PRESERVASI JALAN CIREBON – PALIMANAN – SUMEDANG - Fadli, Adil; Rijaluddin, Arief (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Implementation of bore pile foundation on the Cirebon - Palimanan - Sumedang road Preservation Project is one of the work items for handling landslides which aims to strengthen the retaining wall structure from the load it will carry so that there is no shifting and settlement, the retaining wall structure was built due to the previous existing conditions has experienced a collapse so that a new retaining wall is planned. The foundation used in the construction of retaining walls, namely the bore pile foundation, is a type of deep foundation whose installation is carried out by first drilling the soil with a certain diameter using heavy equipment, bore pile machine until it reaches a predetermined depth, then the assembled steel frame is inserted. drill hole and the next step is casting. The purpose of this study is to find out how the process and method of implementing bore pile foundations in the avalanche handling work of the Cirebon - Palimanan - Sumedang Road Preservation Project. In the method of carrying out bore pile foundations for avalanche handling work on the Cirebon - Palimanan - Sumedang road preservation project, there are several stages of work including preparation, ironing, drilling, casting, and Test Pile.